Pengembangan Instrumen Asesmen Berbasis Literasi Sains Tentang Materi Sistem Ekskresi dan Sistem Pernapasan - Helendra Helendra; D. Ratna Sari (Jurnal Ilmiah Pendidikan Profesi Guru, 2021)
The 2013 curriculum which focuses on improving scientific literacy, assessment is an integral part of the science learning process. However, based on the results of measurements carried out by PISA (Program for International Student Assessment), Indonesian scientific literacy is still relatively low. This study aims to produce an assessment instrument based on scientific literacy on the excretory system and respiratory system material. This research is Research and Development using the Plomp development model which consists of the initial investigation stage, the development stage or the prototyping stage, and the assessment stage. The subjects of the small-scale research product test were 9 students, and the field trial was 32 students. The results showed that the average value of the logical validity of the instrument was 87,23% which was declared very valid and the empirical validity value was 80,00%. The results of the practicality test of the assessment instrument by teachers scored 89,52% and by students 88,43%. The reliability of the scientific literacy-based assessment instrument shows a very high category with a reliability value of 0,93, 80 % questions with moderate difficulty criteria and 66,00% questions with good discriminating power. So, it can be concluded that the scientific literacy-based assessment instrument for the excretory system and respiratory system material can be declared very valid, very practical, and the reliability of the questions is very high.